Use of combined chemotherapy and immunotherapy improves pulmonary arterial hypertension - Tejaswini P. Reddy; Roberto Barrios; Eric Bernicker; Wei Qian; Jenny Chang; Zeenat Safdar (Pulmonary Circulation)
Abstract Treatment modalities for pulmonary arterial hypertension (PAH) improve quality of life and walk distance. However, none of these therapies alter the structural/functional pulmonary vascular integrity that results in vascular remodeling. PAH smooth muscle cells share biological characteristics with cancer cells, which may be potential therapeutic targets for PAH. We present a case of a patient with connective tissue disease (CTD)‐associated PAH treated on triple therapy who developed metastatic lung adenocarcinoma. While on PAH triple‐therapy, she received a combination of carboplatin, pemetrexed, and pembrolizumab. She eventually had a complete pathologic response, no evidence of cancer recurrence, and significant improvement of PAH/overall clinical status. After discontinuation of neoplastic therapy, her clinical status worsened, she eventually passed away, and lung biopsy findings revealed evidence of severe pulmonary smooth muscle cell hypertrophy and pulmonary veno‐occlusive disease. This report suggests that combined chemotherapy and immunotherapy may influence the efficacy of PAH therapies and improve clinical status.